2015
DOI: 10.1155/2015/248529
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders and Polyphenols: Can They Be Helpful in Therapy?

Abstract: The prevalence of psychiatric disorders permanently increases. Polyphenolic compounds can be involved in modulation of mental health including brain plasticity, behaviour, mood, depression, and cognition. In addition to their antioxidant ability other biomodulating properties have been observed. In the pathogenesis of depression disturbance in neurotransmitters, increased inflammatory processes, defects in neurogenesis and synaptic plasticity, mitochondrial dysfunction, and redox imbalance are observed. Ginkgo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 149 publications
2
65
0
2
Order By: Relevance
“…Cells in the central nervous system are more sensitive to toxic effects of ROS, than cells in other organs of the body. 58 The present study revealed an important decrease in GST and CAT activities in brain tissue of ligated female rats. It should be noted also that after 2 weeks of treatment with algae extract in combination with BCG, GST and CAT activities remain significantly lower than that in the control group.…”
Section: G L I G L I G + a E L I G + A E L I G + A E L I G + B C G supporting
confidence: 53%
“…Cells in the central nervous system are more sensitive to toxic effects of ROS, than cells in other organs of the body. 58 The present study revealed an important decrease in GST and CAT activities in brain tissue of ligated female rats. It should be noted also that after 2 weeks of treatment with algae extract in combination with BCG, GST and CAT activities remain significantly lower than that in the control group.…”
Section: G L I G L I G + a E L I G + A E L I G + A E L I G + B C G supporting
confidence: 53%
“…Schizophrenia is a devastating mental disorder, with oxidative stress as part of its pathophysiology. One review reviewed that curcumin may help to alleviate the serious side effects associated with administration of neuroleptics to patients suffering from schizophrenia (Trebaticka & Durackova, ). Results of some meta‐analysis have shown that curcumin is efficacious among depressed patients (Al‐Karawi, Al Mamoori, & Tayyar, ; Q. X. Ng, Koh, Chan, & Ho, ).…”
Section: Introductionmentioning
confidence: 99%
“…The general backbone for flavonoids consists of 15 carbon atoms arranged in two aromatic rings connected by a heterocyclic three-carbon ring. The degree of oxidation of the central pyrol ring differs and leads to the following sub-classification: Flavones, flavonols, isoflavones, flavanones, anthocyanins and flavanols, usually called catechins (29). In plant food products, the major forms are conjugated either with acid-alcohol or with glycosides, sometimes yielding highly complex structures (30).…”
Section: Isoflavones: Structures Sources and General Biological Actimentioning
confidence: 99%
“…The diversity of flavonoid structures undoubtedly contributes to differences in biological efficacy with subtle differences affecting both bioavailability and bioactivity (31). The concept of bioavailability involves several variables, including intestinal absorption, metabolism by intestinal microflora, intestinal and hepatic metabolism, type and nature of circulating metabolites, binding to albumin, cellular uptake, accumulation in tissues and both biliary and urinary excretion (29). Whereas flavonoids are primarily recognized for their antioxidant functions, they also possess antimicrobial and anti-inflammatory activities (32)(33)(34).…”
Section: Isoflavones: Structures Sources and General Biological Actimentioning
confidence: 99%